Assessment of the botanical origin of Saudi Arabian honey samples to identify pollen with chromatographic tools and packing and storage - Alnadhari, Saleh; Abbasova, Gunay; Al-Qahtani, Wahidah H.; Zengin, Gokhan; Islamov, Sokhib; Mammadova, Afat O.; Azad, Abul Kalam; Mammadova, Shakar; Jaradat, Nidal; Babayeva, Ulkar; Humbatov, Mahmud; Ganbarov, Dashgin; et al. (WILEY, 2024)
The increasing demand for honey purification and authentication necessitates the global utilization of advanced processing tools. Common honey processing techniques, such as chromatography, are commonly used to assess the quality and quantity of valuable honey. In this study, 15 honey samples were authenticated using HPLC and GC-MS chromatographic methods to analyze their pollen spectrum. Various monofloral honey samples were collected, including Acacia, Hypoestes, Lavandula, Tamarix, Trifolium, and Ziziphus species, based on accurate identification by apiarists in 2023 from the Kingdom of Saudi Arabia. Honey analysis revealed the extraction of pollen from 20 different honeybee floral species. Pollen identified from honey samples using advanced chromatographic tools revealed dominant vegetation resources: Ziziphus species (23%), Acacia species (25%), Tamarix species (34%), Lavandula species (26%), Hypoestes species (34%), and Trifolium species (31%). This study uses HPLC to extract phenolic compounds, revealing dominant protocatechuic acid (4.71 mg g-1), and GC-MS to analyze organic compounds in honey pollen. Specifically, 2-dodecanone was detected with a retention time of 7.34 min. The utilization of chromatographic tools in assessing honey samples for pollen identification provides a reliable and efficient method for determining their botanical origins, thereby contributing to the quality control and authentication of honey products.
Keywords: chromatography; flavonoids; honey; pollen; SEM; HPLC; BEE; Biochemistry & Molecular Biology; Chemistry; Pharmacology & Pharmacy